Perbandingan Pertanggung-jawaban Pidana terhadap Pelaku Perzinahan Berdasarkan Hukum Pidana Islam Ditinjau dari Perspektif Qanun Aceh Nomor 6 Tahun 2014 dan Hukum Pidana dari Perspektif KUHP: Studi Kasus Putusan Mahkamah Syar’iyah Banda Aceh Perkara Jinayat Nomor 67/JN/2019/Ms.Bna - Ananda Kasmarani Sumby; Rudepel Petrus Leo; Sigit Prabowo Sonbait (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Adultery in Indonesia is discussed from two legal perspectives: Islamic Law (Qanun Jinayah) and Criminal Law from the perspective of the Criminal Code (KUHP). Each has different approaches and rules in regulating criminal liability for adultery. Adultery is considered a betrayal of marriage. The perpetrator of adultery is considered to have abused the trust of his/her spouse and violated the sacred promise of marriage. The type of research the author uses is normative juridical research (library research). This research is also called a document study conducted by examining legal materials by examining theories, concepts and laws and regulations related to this writing through literature studies. The purpose of this research is to understand and develop knowledge about the concept of adultery in Islamic criminal law and to study how the comparison of responsibility for adultery offenders in Islamic criminal law and Indonesian criminal law. The results showed that the punishment contained in Qanun Aceh Number 6 of 2014 is flogging. While Article 284 of the Criminal Code complaints must be made before the expiration of the prosecution period, which is six months from the time the husband or wife finds out about the adultery. Because in addition to the perpetrator of adultery getting a maximum imprisonment of nine months, he can also be subject to a maximum fine of Rp 15,000,000.